MAKNA SIMBOLIK PROSESI UPACARA PANGGIH DALAM PERKAWINAN ADAT JAWA TENGAH DI KECAMATAN KUNTO DARUSSALAM KABUPATEN ROKAN HULU - Merlika Sari; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The summoning ceremony is a tradition that is carried out after the marriage of the Javanese community in the Kunto Darussalam sub-district of Rokan Hulu district, most of the Kunto Darussalam community is dominated by the Javanese tribe community. Talking about the wedding ceremony, can not be separated from the existing cultural elements. Marriage is a ceremonial part of a culture, Javanese culture is full of symbols so it is said that Javanese culture is symbolic culture. The symbols used until now contain values, culture, ethics, and morals that are very important to explain to the next generation. The purpose of this research is to understand the symbolic meaning of the Central Java traditional wedding procession in the Javanese community in Kunto Darusallam District. The subjects used were men or women who carried out the wedding with the Central Java traditional wedding procession and numbered six people and were selected through a purposive sampling technique that had been determined from a predetermined understanding benchmark. The method used in this study is a qualitative method with a symbolic interaction approach. This research was carried out in villages in Kunto Darusallam District, Rokan Hulu Regency.The results of this study indicate that, with the results in symbolic situations which are dividedinto two, namely physical objects in the form of clothing and equipment used in the summoning ceremony and social objects in the form of non-verbal behavior of the bride and groom as the perpetrators of the summoning ceremony or even the family and community who witnessed. Social interpretation of closed actions with the result of external and internal factors, by maintaining culture, togetherness, and customary encouragement, and in open actions seen in the expression of happiness in the faces of perpetrators, families, and Javanese communities in the Kunto Darusallam District, Rokan Hulu District. The procession is implemented in the household as in the procession ofbalangan  gantal,wijik sekar setaman, ngidak tigan, sinduran, kacar kucur, sungkeman, pangkon timbang, dhahar saklimah. The bride who runs each of these stages believes in the harmony of the household later.